Using a Dance Mat to Assess Inhibitory Control of Foot in Young Children - Petraconi, Nathália; Giorjiani, Giuliana Martinatti; Saad, Andressa Gouveia de Faria; Scardovelli, Terigi Augusto; Gomes da Silva, Sérgio; Balardin, Joana Bisol (Frontiers in Physiology, 2019)
The development of motor response inhibition is critical during preschool years and has been associated with an improvement in gross motor coordination in this population. However, the assessment of inhibitory abilities in young children is challenging in terms of task selection and subject engagement, especially when investigating foot responses. Thus, the aim of this study was to describe a child-friendly Go/No-Go paradigm to assess inhibitory control of foot based on a dance mat protocol. In this method, Go and No-go stimuli are modeled in the context of a fishing game, and behavioral responses are assessed by recording the latency to touch the mat and the accuracy of the touches. In this protocol article, we 1) describe the stages of the experimental set-up, 2) provide an illustrative data collection example in a sample of children aged 3-4 years, and 3) describe how to process the data generated. The utilization of the dance mat provides a feasible tool for researchers interested in studying the development of motor inhibitory control of foot in preschoolers. Potential applications of this protocol may include studies on developmental differences between hand and foot specialization, sports-related performance and neuroimaging.